Suplementação de vacas f1 holandês x zebu com suplementos nitrogenados e monensina sódica: produção e composição do leite - Aline Nazareth Rodrigues (2011)
The objectives of the present study were to evaluate the production and the composition of milk produced by F1 Holstein vs Zebu cows. Cows (n=15) were fed concentrate at milking time and corn silage added or not of nitrogenated supplements with or without monensin. The cows with 21 days in milk and producing inicially 19.2 kg of milk daily were distributed in 5x5 Latin square. The diets were: concentrate and corn silage (C.SM), C.SM + nitromineral (C.SMNM), C.SM + nitroprotein (C.SMNP), C.SMNM + monensin (C.SMNM+MO) and C.SMNP + MO. The use of C.SMNP increased the milk production in relation to C.SM (P<0,05) The C.SMNP cows produced less milk then C.SMNM cows (16,69 vs 15,59; P< 0,05). The concentration of milk urea nitrogen (NUL) of cows fed C.SMNM and C.SMNP increased 2.64% and 3,56% (P<0,05) respectively, in relation to C.SM cows. The use of MO did not affect the production and the milk composition (P> 0.05). The addition of monensin do C.SMNP diet increased the milk long-chain fatty acid mainly the isomer C18: 2 cis-9. cis-12 by 0,08% and the conjugated linoleic acid.(CLA) C The other milk constituents and blood glucose were not affected by any treatment. There was alteration in the profile of long-chain fatty acids was for the isomers of (CLA), C18: 2 cis-9, trans-11 by 0.07% (P<0,05). Cows that had C.SMNP+MO diet had milk with increased CLA.